DEVELOPMENT OF A PROJECT-BASED CONTEXTUAL TEACHING AND LEARNING MODEL TO IMPROVE ENGLISH WRITING SKILL - Murnia Suri; Rafni Fajriati; Fitriliana Fitriliana; Emilia Aini (Universitas Ubudiyah Indonesia, 2026)
This study aims to develop and examine the effectiveness of a Contextual Teaching and Learning (CTL) model integrated with Project-Based Learning (PjBL) in improving students’ English writing skills. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants of this study were 69 students from the Public Health Study Program at Universitas Ubudiyah Indonesia. The instruments used in this study included writing tests (pre-test and post-test), observation and questionnaires. The results showed that the mean score of the pre-test was 54.2, which increased to 76.8 in the post-test. The result of the paired sample t-test indicated that the improvement was statistically significant. In addition, the observation results revealed that students were more active and engaged during the learning process, while the questionnaire results showed positive responses toward the implemented learning model. In conclusion, the CTL model integrated with Project-Based Learning is effective in improving students’ English writing skills. It also enhances students’ motivation, participation, and engagement in the learning process, particularly in the context of higher education. Keys words: Contextual Teaching and Learning; Project-Based Learning; Writing Skills; Instructional Model Development